Surgical versus conservative interventions for treating tibial shaft fractures in adults - Raju, Karthickeyan (Cochrane Database Syst Rev, 2018)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To assess the effects (benefits and harms) of surgical versus conservative interventions for treating tibial shaft fractures in adults.